2019
DOI: 10.1002/jaba.628
|View full text |Cite
|
Sign up to set email alerts
|

Increasing compliance with wearing a medical device in children with autism

Abstract: Health professionals often recommend the use of medical devices to assess the health, monitor the well-being, or improve the quality of life of their patients. Children with autism may present challenges in these situations as their sensory peculiarities may increase refusals to wear such devices. To address this issue, we systematically replicated prior research by examining the effects of differential reinforcement of other behavior (DRO) to increase compliance with wearing a heart rate monitor in 2 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…For all participants, the DRO intervention did not require the introduction of response blocking (i.e., escape extinction procedures). This study replicates and extends previous literature supporting the effectiveness of differential reinforcement with and without fading and without the use of response blocking to increase compliance (Dufour & Lanovaz, 2020;Hagopian & Thomson, 1999;Lalli et al, 1999;Piazza et al, 1997;Shabani & Fisher, 2006;Slifer et al, 1993).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For all participants, the DRO intervention did not require the introduction of response blocking (i.e., escape extinction procedures). This study replicates and extends previous literature supporting the effectiveness of differential reinforcement with and without fading and without the use of response blocking to increase compliance (Dufour & Lanovaz, 2020;Hagopian & Thomson, 1999;Lalli et al, 1999;Piazza et al, 1997;Shabani & Fisher, 2006;Slifer et al, 1993).…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, the authors included a modified stimulus fading procedure in which each step of the medical exam was gradually introduced to the participant to increase compliance to socially significant levels. As with Dufour and Lanovaz (2020), their results indicated that escape extinction was not necessary to increase compliance with the medical exam process. Similar interventions without escape extinction have also been used to increase compliance with other medical procedures (cystic fibrosis treatment; Hagopian & Thompson, 1999; functional magnetic resonance imaging [fMRI]; Cox et al, 2017;Slifer et al, 2002;hemodialysis;Carton & Schweitzer, 1996;needle phobia;Shabani & Fisher, 2006;pediatric neuroimaging;Slifer et al, 1993).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This study utilized a head-mounted eye tracker to record the gaze behavior, which might affect the social behavior of children with ASD to a larger extent. In general, individuals with ASD are more sensitive to wearing devices and eye-tracking techniques usually require extensive calibration [ 38 , 39 ]. These issues considerably raise the difficulty of implementing eye-tracking techniques on children with ASD, particularly on the younger population.…”
Section: Discussionmentioning
confidence: 99%
“…Respondent conditioning interventions may also include operant conditioning components to strengthen nonavoidant and compliant behavior. Contingent reinforcement for nonavoidant and compliant behavior (i.e., operant differential reinforcement of an alternative or other behavior) is commonly used (Davis & Ollendick, 2005; Dufour, & Lanovaz, 2020). In addition, noncontingent reinforcement is associated with increased compliance (e.g., Nipe et al, 2018).…”
mentioning
confidence: 99%